THE EFFECTS OF PROGRAMMED WORK ON THE DEVELOPMENT OF BASIC MOTOR SKILLS IN YOUNG FOOTBALL PLAYERS - Emin Mujezinović; Alen Kapidžić; Melika Muratović; Edin Užičanin; Fuad Babajic (Sport Scientific And Practical Aspects, 2025)
The aim of this research was to determine the effects of programmed work on the development of basic motor skills in young soccer players. The sample of participants in this research were football players aged 11 and 12 and they were divided into two equal groups of 30 entities. All participants are involved in a systematic training process in their football clubs. The research problem was to determine whether there are positive effects of programmed work on the development of basic motor skills. A total of 16 variables from the area of basic motor skills were used in the research. The experimental work program was carried out over a period of three months and included 38 training units. After initial testing and successfully implemented programmed work and final testing, a significant impact of programmed work on the development of basic (fundamental) motor skills was determined. In general, looking at the total motor abilities that were evaluated from 16 variables in the experimental group, a statistically significant difference was achieved in 11 variables, in the control group 6 with a positive significant difference